2017
DOI: 10.19173/irrodl.v18i2.2891
|View full text |Cite
|
Sign up to set email alerts
|

Student Voices on the Roles of Instructors in Asynchronous Learning Environments in the 21st Century

Abstract: This paper determines which instructional roles and outputs are important in the 21 st century from the perspective of students in asynchronous learning environments. This research work uses a literature review, in-depth interviews with experts, and a pilot study with students to define the instructors' outputs. Following this, roles are determined by using a quantitative methodology (in a sample of 925 students). To our knowledge, the remaining research works on this topic identify the online instructors' rol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
27
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(32 citation statements)
references
References 29 publications
(3 reference statements)
4
27
0
1
Order By: Relevance
“…Concerning the usefulness of the instructors' feedback, the analysis of focus group interview data reveals that the learners of this course valued the instructors' messages. This finding matches those observed in other studies (Ghadirian et al, 2017;Gómez-Rey et al, 2017) which showed that learners participated more if instructors' posts were of high quality and usefulness. In this study, however, the majority of instructors' messages, interestingly, aimed to inform the learners about their study progress, to respond to technical questions and remind students about undone exercises.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Concerning the usefulness of the instructors' feedback, the analysis of focus group interview data reveals that the learners of this course valued the instructors' messages. This finding matches those observed in other studies (Ghadirian et al, 2017;Gómez-Rey et al, 2017) which showed that learners participated more if instructors' posts were of high quality and usefulness. In this study, however, the majority of instructors' messages, interestingly, aimed to inform the learners about their study progress, to respond to technical questions and remind students about undone exercises.…”
Section: Discussionsupporting
confidence: 91%
“…In this study, the majority of learners also placed a high level of importance on the regularity of instructors' online presence. These findings seem to be consistent with other research which found that the instructors' teaching presence plays a crucial role in pedagogical instruction, using different types of interactional matrices (Cox et al, 2015;Gómez-Rey, 2017). However, the instructors themselves had different levels of online presence: some were online only twice a week.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Furthermore, online tutor's role fulfills several functions like: a) academic: relating to mastery of contents, activities and student formative assessment, b) technical: mastery over available tools on the virtual environment, c) guiding: plan, structure and establish operating rules, d) social: meant to overcome feelings of isolation, loss or lack of motivation of students participating in this educational mode, and e) organizational: providing students guidance and advice on organizational matters in the course of the formative actions ( Gómez-Rey et al., 2017 ; Gulbahar and Kalelioglu, 2015 ; Klimova and Poulova, 2011 ; Krasnova and Demeshko, 2015 ).…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Information technology has facilitated a variety of new learning approaches that allow students to develop naturally driven by their own interests (Fidaldo & Thormann, 2017;Gómez-rey et al, 2017;Yadegaridehkordi et al, 2015). They can find a wide range of knowledge through independent thinking and real-world experience.…”
Section: Introductionmentioning
confidence: 99%